A human cyber physical system framework for operator 4.0 – artificial intelligence symbiosis. (August 2020) - Bousdekis, Alexandros; Apostolou, Dimitris; Mentzas, Gregoris
Abstract: The emergence of Artificial Intelligence (AI) reveals new opportunities in Industry 4.0 environments. However, the lack of appropriate data and the requirements for trustworthiness pose significant challenges in the applicability and the effectiveness of AI systems in manufacturing environments. On the other hand, Industry 4.0 enables new types of interactions between humans and AI, but also between digital and physical worlds in the context of Cyber Physical Systems (CPS). In this paper, a Human Cyber Physical System (HCPS) framework for Operator 4.0 – Artificial Intelligence Symbiosis is proposed and its main architectural building blocks are described.